2021
DOI: 10.5219/1686
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of agri-food foreign trade in conditions of the Slovak Republic

Abstract: The presented paper aims to evaluate the development and competitiveness of agri-food foreign trade of the Slovak Republic for the period 2016 – 2020. In the article, we present the priorities of Slovakia within the commodity structure. We use the RCA indicator to identify comparative advantages. In this paper, we also compare the actual and estimated development of agri-food foreign trade of the Slovak Republic in the years 2018 – 2020. Based on the reached results, we can state that we achieve an ever-increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Nagyová, et al [65] confirmed that emotions are a significant factor 'influencing consumers' decisions and even changing them. This fact creates space for the growth of selected companies and the needed development of Slovak agricultural foreign trade [66]. This study aims to determine the CSR activities of the company Plzenský Prazdroj which can be effectively used in marketing communication toward millennial consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Nagyová, et al [65] confirmed that emotions are a significant factor 'influencing consumers' decisions and even changing them. This fact creates space for the growth of selected companies and the needed development of Slovak agricultural foreign trade [66]. This study aims to determine the CSR activities of the company Plzenský Prazdroj which can be effectively used in marketing communication toward millennial consumers.…”
Section: Resultsmentioning
confidence: 99%